Entre inverno e verão: comunidades tradicionais, pesca artesanal e uso de recursos comuns no Parque Nacional dos Lençóis Maranhenses - MENDES, Diana Patrícia (2018)
This study seeks to understand the rules that govern the use of common resources in combination with private family appropriation involving artisanal fishing practiced by families from the village of Mocambo, located in the Lençóis Maranhense National Park in the municipality of Barreirinhas. There is, in this village, a biophysical environment with the presence of so-called wells, lakes, ponds and reservoirs where the families carry out freshwater fishing activities. Besides these, they also use the Negro River as a fishing place in an artisanal way. In the fishing environments referred to above, the elements of nature are appropriate, combining forms of common use with private family ownership. The discussions here take into account the seasonality, from what they term winter and summer. In these periods there is a constant change in the landscape in Mocambo, as in other localities of the Park, that interfere in the fishing activities, providing expectations of law in relation to the environments and the ways of use. In the development of artisanal fisheries it is observed that the use of aquatic environments within a social and natural space is a result of the combination of private family ownership with those forms of common use of resources. Thus, taking as reference the artisanal fishing, the work will seek to account for the rules that guide the characterization of the property regime operated by the families of Mocambo, seeking to reflect on the sense of common property, common use of resources and private family ownership.